2021
DOI: 10.1073/pnas.2114997119
|View full text |Cite
|
Sign up to set email alerts
|

The sacrificial adaptor protein Skp functions to remove stalled substrates from the β-barrel assembly machine

Abstract: The biogenesis of integral β-barrel outer membrane proteins (OMPs) in gram-negative bacteria requires transport by molecular chaperones across the aqueous periplasmic space. Owing in part to the extensive functional redundancy within the periplasmic chaperone network, specific roles for molecular chaperones in OMP quality control and assembly have remained largely elusive. Here, by deliberately perturbing the OMP assembly process through use of multiple folding-defective substrates, we have identified a role f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 73 publications
0
16
1
Order By: Relevance
“…It is also possible that FkpA-uOMP complexes have the capacity to be fully degraded by DegP as has recently been shown for tightly-bound Skp-uOMP complexes (Figure 7). 67 Previous work has suggested that the chaperone function of FkpA is localized to either the N-terminal dimerization 26,27 or the C-terminal PPIase domain, 24,28 but we find that neither domain alone exhibits chaperone function nor high affinity uOmpA171 binding. Some binding of uOmpA171 to N-FkpA was observed even though it was 10-fold weaker than the binding of the full-length protein, which may explain why N-FkpA prevented protein aggregation in some in vitro assays but was unable to rescue periplasmic stress when introduced into a ΔfkpA ΔdegP deletion strain.…”
Section: Discussioncontrasting
confidence: 73%
“…It is also possible that FkpA-uOMP complexes have the capacity to be fully degraded by DegP as has recently been shown for tightly-bound Skp-uOMP complexes (Figure 7). 67 Previous work has suggested that the chaperone function of FkpA is localized to either the N-terminal dimerization 26,27 or the C-terminal PPIase domain, 24,28 but we find that neither domain alone exhibits chaperone function nor high affinity uOmpA171 binding. Some binding of uOmpA171 to N-FkpA was observed even though it was 10-fold weaker than the binding of the full-length protein, which may explain why N-FkpA prevented protein aggregation in some in vitro assays but was unable to rescue periplasmic stress when introduced into a ΔfkpA ΔdegP deletion strain.…”
Section: Discussioncontrasting
confidence: 73%
“…S5C and S5D). Based on the observation that the elimination of the periplasmic chaperone Skp reduces the degradation of OMPs that contain β signal mutations and enhances their assembly (13,14), we next wished to see if the level of the split OmpA mutants would increase in strain XW102 (MC4100 ΔompA J o u r n a l P r e -p r o o f Δskp). Interestingly, the assembly of the single mutants was almost completely restored, while the folded form of the double mutant became detectable (Figs.…”
Section: Split Ompa Is Integrated Into the Om By The Bam Complexmentioning
confidence: 99%
“…Skp is a jellyfish-like homotrimer that can accommodate unfolded or partially folded OMPs in its central cavity to protect them from misfolding in the aqueous environment ( 11 , 12 ). Skp either transfers OMPs to other chaperones such as SurA or identifies defective OMPs and directs them to proteases for degradation ( 13 , 14 ). SurA targets OMPs to a heteroligomer known as the b arrel a ssembly m achinery (Bam) complex that catalyzes their insertion into the OM.…”
mentioning
confidence: 99%
“…Although no OMP essentially depends on Skp in the presence of SurA ( Denoncin et al, 2012 ; He & Hiller, 2018 ), other moonlighting activities have been suggested exclusively for Skp. Recently, the chaperone has been described as an adaptor protein that delivers the misfolded OMP LamB to the periplasmic protease DegP ( Combs & Silhavy, 2022 ). Skp is a potent disaggregase of OmpC and OmpX ( Li et al, 2018 ; Chamachi et al, 2022 ) and it also demonstrates the holdase and disaggregase activity towards several soluble proteins ( Purdy et al, 2007 ; Wagner et al, 2009 ; Entzminger et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%